Synthesis of New Heterocyclic Thiazolidinone and Azetidinone Compounds and Their Antibacterial Activity - MEHTA, K.H.; DESAI, K.R. (Asian Journal of Chemistry, 2010)
Thiazolidinones and azetidinones have been prepared by the reaction of various Schiff bases with tbioglycolic acid and chIoroacetyl chloride respectively. The intermediate Schiff bases were synthesised by the condensation of diammo dipbenyl methane with various pyrazolines. The structures of the compounds have been confirmed by elemental analysis and spectral analysis. The antibacterial activity of the compounds has also been screenend.